Puzzle Media on Early Childhood Cognitive Abilities - Jumaedah, Jumaedah; Herlina, Herlina; Herman, Herman; Wahira, Wahira; Darwis, Assidiq (Journal of Education Method and Learning Strategy, 2026)
Puzzles stimulate children to recognize relationships between parts and wholes, understand patterns and shapes, hone visual memory skills, practice cause-and-effect logic, and develop simple strategies through trial and error. This study aims to determine the cognitive abilities of children in the control group and the experimental group before and after being given learning using puzzle media. The type of research used is quantitative with quasi-experimental design or pseudo-experimental research. Using data collection techniques in the form of observations, tests, interviews, and documents. The data analysis used goes through two stages, namely descriptive statistical analysis and inferential analysis. Descriptive analysis is used to provide an overview of children's cognitive development, while inferential analysis is used to test hypotheses whether there is a significant difference between the experimental group (puzzle media) and the control group (conventional learning). The results showed that the gross motor development of children aged 5-6 years after participating in learning with fuzzle media  in the experimental group could be said to be significant based on the results  of the paired sample t test with a p-value smaller than the significance level of 5%. The gross motor development of children aged 5-6 years after participating in learning with conventional media can be said to be significant based on the results  of the Wilcoxon Signed Rank test with a p-value greater than the significance level of 5%. Based on the results  of the Independent Sample T-Test, it was found  that the p-value was smaller than the significance level of 5%, so there was a significant difference in the cognitive development of children aged 5-6 years between the groups that participated in learning using fuzzle media and conventional media.